1973
DOI: 10.1002/mrc.1270051212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field on chemical reactions

Abstract: Abstract-The effect of the magnetic field on CIDNP can be found in many chemical reactions. It is considered to result from the fact that the probability of singlet-triplet transitions in a radical pair is determined by magnetic interactions in the pair and is field strength dependent. In the present communication we wish to demonstrate that for the same reason the external magnetic field can also markedly affect the rates of chemical reactions involving free radicals.WE INVESTIGATED the reactions of substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…The radical pair mechanism is common for a large variety of MFE effects (CIDNP and CIDEP [16], RYDMR [17,18], magnetic isotope effect on radical recombination reaction yield [19] and paramagnetic additives effects on the RRR [32]). All depend on the existence of the spin-correlated RP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The radical pair mechanism is common for a large variety of MFE effects (CIDNP and CIDEP [16], RYDMR [17,18], magnetic isotope effect on radical recombination reaction yield [19] and paramagnetic additives effects on the RRR [32]). All depend on the existence of the spin-correlated RP.…”
Section: Resultsmentioning
confidence: 99%
“…Any perturbation which affects this crucial spin-mixing stage might affect the yield of the RRR. This also depends on optimising the re-encounter rate in the diffusion process within the geminate RP solvent cage [16,50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical illustration of the type of effects observed is provided by the work of Sagdeev et al [100,101] on the reaction of benzyl chloride with nbutyllithium. The mechanism of this reaction is summarized in the scheme of Figure 4.…”
Section: The Mechanistic Role Of Outer Sphere Complexesmentioning
confidence: 99%
“…If there is interstate crossing to the triplet state the radicals can diffuse apart and eventually react to give symmetric products. Sagdeev et al [101] found for the reaction of pentafluorobenzyl chloride with n-butyl lithium that the ratio of the amount of unsymmetrical pro-RC1 + n-BuLi Square brackets indicate outer sphere complex [101].…”
Section: The Mechanistic Role Of Outer Sphere Complexesmentioning
confidence: 99%